Antenatal optimisation for preterm infants less than 34 weeks: a quality improvement toolkit. - Shaw, Lauren; Becher, Julie-Clare (Infant, 2020)
The British Association of Perinatal Medicine (BAPM) and the National Neonatal Audit Programme (NNAP) are collaborating on four quality improvement toolkits to support perinatal staff to implement the evidence around perinatal optimisation. This article presents the Antenatal Optimisation Toolkit. The evidence for key interventions is described alongside a quality improvement journey, which supports staff to choose improvement solutions most suitable for the local context.